G57(P) Nurses leading the way: assessing the impact of a nurse-led neutropenic sepsis pathway on achieving the 'golden hour' in a paediatric emergency department. (May 2019) - Jefferson, LR; Walker, H; Spires, H; Jones, K; Christian, W
Abstract : Aims: To improve patient safety by reducing our time to blood sampling and antibiotic administration in children with suspected neutropenic sepsis through the introduction of a nurse-led pathway. Methods: Initial audit of performance against standard for time to triage, blood sampling, medical review and antibiotic administration for children with suspected neutropenic sepsis was performed using trust electronic records. Analysis of these results demonstrated failure to meet internal and national targets. Subsequent multidisciplinary discussion between the emergency, oncology and nursing staff led to 3 interventions being implemented: a new pathway to empower nurses to treat prior to doctor review; adopting national rather than local targets (from 30 to 60 min); and increasing nursing competency training. A re-audit then took place. Results: See table 1 . Conclusion: Initial audit results identified a poor attainment of standards. The 3 main barriers identified were difficulty accessing central access due to insufficient training, varying practice amongst medical teams, and delay to treatment caused by awaiting medical review. Our interventions were focused on nursing staff. In this cohort of patients establishing criteria led management meant we were able to remove unnecessary barriers and empower nurses to act. Empowering nurses through increased training and providing a guideline for treatment has proved pivotal in increasing the department's ability to attain its standards. Factoring in the change in standard by comparing the initial audit to the adjusted standard still showed that significant improvements were made following our interventions. Feedback from nursing staff has been positive and highlights ease of use, empowerment of nursing staff and consistency of advice. We expect further improvement as staff become more aware of the change in practice and are excited to utilise our success to expand nurse-led interventions within the department.